Mediamorphosis the dynamics of communication and socio-cultural change - Pusta, Maria Gwenetha Ybanez; Revilla, Maria Virginia A (Malabon City Mutya Pubishing House, Inc., 2014)
"It tackles the role of mas media as an agent oof change and as a catalyst of development, in the light of contemporary communication, critical and cultural theories."--Preface
Includes bibliographical references.
Keywords: Mass media; Communication; Mass media -- Technological innovations; Mass media -- Social aspects